2002
DOI: 10.3171/spi.2002.96.1.0131
|View full text |Cite
|
Sign up to set email alerts
|

Polymethylmethacrylate-augmented screw fixation for stabilization in metastatic spinal tumors

Abstract: ✓ Screw fixation augmented with polymethylmethacrylate (PMMA) or some other biocompatible bone cement has been used in patients with osteoporosis requiring spinal fusion. No clinical studies have been conducted on PMMA-augmented screw fixation for stabilization of the vertebral column in patients with metastatic spinal tumors. The purpose of this study was to determine whether screw fixation augmented with PMMA might be suitable in patients treated for multilevel metastatic sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 14 publications
(21 reference statements)
0
8
0
Order By: Relevance
“…Nevertheless, there is frequently a need to use K-wires or screws to improve MMA anchorage to the adjacent VBs. 19 Because MMA may "piston" in the setting of weak bone, the pins may migrate to penetrate vital structures (spinal cord, aorta). The chest tube technique 16 and our own modifications (endplate preparation, then distraction, then placement of MMA against endplates, then compression with ventral or dorsal instrumentation) avoid the use of anchoring pins and their associated risks (Fig.…”
Section: Types Of Reconstructionmentioning
confidence: 99%
“…Nevertheless, there is frequently a need to use K-wires or screws to improve MMA anchorage to the adjacent VBs. 19 Because MMA may "piston" in the setting of weak bone, the pins may migrate to penetrate vital structures (spinal cord, aorta). The chest tube technique 16 and our own modifications (endplate preparation, then distraction, then placement of MMA against endplates, then compression with ventral or dorsal instrumentation) avoid the use of anchoring pins and their associated risks (Fig.…”
Section: Types Of Reconstructionmentioning
confidence: 99%
“…PMMA bone cement has been used to augment screw fixation in spine [4,10,16,18,19,22] and trauma [3,7,15,17] applications. These studies all showed increases in failure strength of constructs augmented with PMMA.…”
Section: Introductionmentioning
confidence: 99%
“…2 PMMA has had limited use as a reconstructive and stabilizing material in the treatment of cervical spine degenerative diseases, but has been recently used for the treatment of osteoporosis fractures. 15,16 For a bone graft to be successful, three processes, osteogenesis, osteoconductivity, and osteoinductivity, which mimic the natural events that occur in cancellous bone, must take place. 10,11 We simulated the combined characteristics of bone grafts and cages by using shaped hollow bone cement filled with impacted cancellous bone as a substitute for structural bone graft.…”
Section: Discussionmentioning
confidence: 99%